Pseudocyst of pinna: a clinical experience - Showkat, Showkat Ahmad; Dar, Nissar Husain; Shafi, Omar Mohammed (International Journal of Research in Medical Sciences, 2019)
Background: Pseudocyst of pinna is an intracartilagenous accumulation of fluid in pinna and is hardly encountered in routine ENT practice. The etiology is unclear. It is seen to affect most commonly middle-aged males. Medical treatment is ineffective. Various treatments are suggested in the literature. The aims of the paper were to study the clinical and demographic characteristic of patients with pseudocysts. Methods: Forty patients were diagnosed with pseudocyst of the auricle between July 2016 and July 2019 on the basis of clinical characteristics, colour of aspirated fluid and absence of infection. Clinical and demographic characteristics were noted. Results: Out of 40 patients only five were females. Involvement of left side was seen more than right one. None had bilateral involvement. Adults in the age group of 31-45 were commonly affected. Most common site of involvement was triangular fossa. Conclusions: Pseudocyst of the pinna is a benign condition characterized by intracartilagenous accumulation of fluid. The disease is seen commonly unilaterally in middle aged males. Many modalities of treatment have been recommended in the literature with varied recurrence and failure rates.